2014
DOI: 10.1089/lrb.2013.0045
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Properties of Rat Mesenteric Lymphatic Vessels and their Regulation by Stretch

Abstract: Background: In mammals, lymph is propelled centrally primarily via the phasic contractions of collecting lymphatic vessels, known as lymphatic pumping. Electrophysiological studies conducted in guinea pig and sheep mesenteric lymphatic vessels indicate that contractions are initiated in the lymphatic muscle by nifedipine-sensitive action potentials (APs). Lymphatic pumping is highly sensitive to luminal fluid loading and the mechanical properties of this stretch-induced pumping have been consistently studied, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 31 publications
4
47
0
Order By: Relevance
“…31,32 Ca 2 + movement via the L-type channels has been thought to contribute significantly to the regulation of lymphatic pump activity, while intracellular Ca 2 + flux plays a less significant role that may be modified by transmural pressure. 16,17 Our observations confirm that sarcolemmal Ca 2 + entry via L-type Ca 2 + channels contributes to the spontaneous Ca 2 + transients that precede lymphatic phasic contractions. Studies on mesenteric lymphatic vessels using wire myograph have shown that nifedipine in rats (10 -6 M) 16 and in humans (3 · 10 -9 M) 33 abolishes lymphatic pumping.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…31,32 Ca 2 + movement via the L-type channels has been thought to contribute significantly to the regulation of lymphatic pump activity, while intracellular Ca 2 + flux plays a less significant role that may be modified by transmural pressure. 16,17 Our observations confirm that sarcolemmal Ca 2 + entry via L-type Ca 2 + channels contributes to the spontaneous Ca 2 + transients that precede lymphatic phasic contractions. Studies on mesenteric lymphatic vessels using wire myograph have shown that nifedipine in rats (10 -6 M) 16 and in humans (3 · 10 -9 M) 33 abolishes lymphatic pumping.…”
Section: Discussionsupporting
confidence: 71%
“…16,17 Our observations confirm that sarcolemmal Ca 2 + entry via L-type Ca 2 + channels contributes to the spontaneous Ca 2 + transients that precede lymphatic phasic contractions. Studies on mesenteric lymphatic vessels using wire myograph have shown that nifedipine in rats (10 -6 M) 16 and in humans (3 · 10 -9 M) 33 abolishes lymphatic pumping. Our findings with the lymphatic vessels isolated from rats that did not receive alcohol reflect the results of Atchison and Johnston, who used isolated bovine mesenteric lymphatic vessels and observed that nifedipine, applied at the same concentration we used, decreased both contraction frequency and amplitude of contraction.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…There is evidence that the lymphatic muscle cells are originated from mesenchymal progenitors [97]. There is also evidence that electrical action potentials trigger lymphatic smooth muscle contractions and vice versa [98]. In fact, the spontaneous and intrinsic nature/origin of these contractions suggests that each action potential/(rhythmic contraction) is preceded by a pacemaker event, like cardiac contraction (see Figure 2 of [96]).…”
Section: How and When Is The Lymphatic System Developedmentioning
confidence: 99%
“…Lymphatic drainage involves active contractile pumping, both in animal models [9][10][11][12] and human limbs. 13 To assess lymphatic collector vessel pump function in the upper limbs of women with established BCRL, pump function was quantified as the maximum pressure (Ppump) generated in the collector lymphatics when lymph flow was blocked by inflating a cuff around the upper arm (lymphatic congestion lymphoscintigraphy 14 )…”
Section: Introductionmentioning
confidence: 99%